Digital forensics and incident response : incident response techniques and procedures to respond to modern cyber threats - Johansen, Gerard (Packt Publishing Ltd., 2020)
An understanding of how digital forensics integrates with the overall response to cybersecurity incidents is a must for all organizations. This book offers concrete and detailed guidance on how to conduct the full spectrum of incident response and digital forensic activities.